Adsorption study of some inorganic elements on the surface of activated charcoal prepared from ceratonia siliqua - Sarhan A Salman; Faiz M Hameed; Wesam F Ahmed (Tikrit Journal of Pure Science)
This study included the process of adsorption of some inorganic elements known as environmental risk (Cd, Cr, Cb, Pb) of its water solutions on the surface of activated charcool to ceratonia siliqua . The percentage of adsorption and isothermal adsorption curves were calculated according to equation, as well as the effect of temperature , pH and particle size of adsorbent on the adsorption of these elements. The study included the comparative study of the adsorption with natural ceratonia siliqua powder. The results showed an optimum conditions at PH=5 and the partical size of adsorbent was 500 μm, while the percentage of adsorption ranged from 81% to 93%